Pengaruh Hybrid Working Dan Motivasi Kerja Terhadap Kinerja Karyawan Dimediasi Kepuasan Kerja Pada PT Digital Visma Media (DVM) - DwiGraha. M, Yogi Bima; Js Pareke, Fahrudin; Praningrum (Universitas Bengkulu, 2025)
PT Digital Visma Media (DVM) is a creative media company engaged in digital content production and marketing services. With the rise of the hybrid working trend—a combination of remote and in-office work—questions arise regarding its impact on employee performance. Furthermore, work motivation and job satisfaction are also crucial factors in determining organizational effectiveness. Therefore, this study aims to evaluate the influence of hybrid working and work motivation on employee performa.This study employs a quantitative descriptive method, with data collected through questionnaires distributed to 395 employees of PT Digital Visma Media. A purposive sampling technique was used for sample selection, and data were analyzed using SEM-PLS 4.1.0.8 for Windows. The findings indicate that hybrid working and work motivation have a positive and significant impact on employee performance. Additionally, hybrid working positively influences job satisfaction, which in turn enhances employee performan.These findings affirm that an effective implementation of hybrid working, along with improved work motivation, can enhance both employee performance and job satisfaction. Therefore, PT Digital Visma Media needs to develop better policy strategies to optimize the implementation of hybrid working, maintain work motivation levels, and ensure job satisfaction to enhance overall organizational performance.